Komunikasi Kenusantaraan (Studi Komunikasi Nusantara Perspektif Integrasi Interkoneksi) - Mokhamad Mahfud (Aplikasia)
The term "think globally and act locally" has begun to surface since the eighties, but until now, a quarter century later, there was also a surefire formula go see about it. Human experience feel things that otherwise like sara (suku, agama dan ras)  events that befall the nation, instead of peace, mutual trust, peaceful coexistence, at-ta'ayus as-silmi, tolerance, tasamuh among fellow human beings and between groups, but rather violence, violence , prejudice (prejudice), az- su'u zan  religion, ethnicity, class, race, interests, both at the local, regional, national and even international (global). As if all want to reverse the adage "think locally and act only", without having coupled "think globally". In the associate, connect and communicate with other groups and do not feel the need to consider the governance rules, laws, agreements and international relations.